1999
DOI: 10.1161/01.str.30.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Trends of Ischemic Stroke and Transient Ischemic Attacks in a Well-Defined French Population From 1985 Through 1994

Abstract: Background and Purpose-The changing incidence of ischemic stroke is of major concern in view of its public health impact, to define the population concerned, to identify risk factors, and to set up health-care systems. The aim of this study was to evaluate the time trends associated with the incidence of all the subtypes of ischemic stroke and transient ischemic attacks in a well-defined population for 10 years. Methods-Since 1985, a population registry has recorded each patient living in Dijon (France) who su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…4,20 The overall TIA incidence rate in Novosibirsk adjusted to the European population (27/100 000; 95% CI, 9 to 79) is similar to that reported in a population-based study in Spain (21/100 000; 95% CI, 12 to 30) 7 and Italy (42/100 000; 95% CI, 33 to 54). 5 In Dijon, France, the world-standardized incidence of TIA over the 10-year period (1985-1994) 2 varied from 8.4 to 29.2 cases per 100 000 residents per year in men and from 3.9 to 18.8 cases per 100 000 residents per year in women, but these changes were not statistically significant. However, the mean age of TIA patients in Novosibirsk (62 years in men and 66 years in women) appears to be lower than that in some European countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,20 The overall TIA incidence rate in Novosibirsk adjusted to the European population (27/100 000; 95% CI, 9 to 79) is similar to that reported in a population-based study in Spain (21/100 000; 95% CI, 12 to 30) 7 and Italy (42/100 000; 95% CI, 33 to 54). 5 In Dijon, France, the world-standardized incidence of TIA over the 10-year period (1985-1994) 2 varied from 8.4 to 29.2 cases per 100 000 residents per year in men and from 3.9 to 18.8 cases per 100 000 residents per year in women, but these changes were not statistically significant. However, the mean age of TIA patients in Novosibirsk (62 years in men and 66 years in women) appears to be lower than that in some European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Although incidence of TIA has been reported for numerous sites worldwide, only few incident population-based studies on TIA in all age groups of the population have been reported thus far. [1][2][3][4][5][6][7][8][9][10][11] No such data in Russia have ever been published in the international literature. However, data on TIA incidence trends are important in determining mechanisms and factors responsible for the occurrence of this disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Stroke incidence also appeared to decline in the 1960s and 1970s in the United States, 6,7 Asia, 8 and Europe, 9 -11 but this latter decline has also leveled off, and most studies during the 1980s and 1990s have shown either no change [12][13][14][15][16] or more commonly an increase in age-and sex-adjusted incidence. [17][18][19][20][21][22][23][24][25][26] In contrast, UK stroke mortality rates based on death certification have declined steeply in recent decades. 2,27 The decline in the UK appears to be consistent with a 40% decline in population-based stroke incidence and mortality in Oxfordshire, UK, between 1981 to 2004 and 2002 to 2004, 28 but national mortality data could have overestimated the time trends in the UK as a whole because of changes in the practice of death certification.…”
mentioning
confidence: 99%
“…Although all patterns were largely due to the older age of our population, other reasons should be considered: diligent case ascertainment, complete screening procedures, and extensive use of cardiovascular examination, together with the progressive increase of cardioembolic stroke incidence in the general population, registered in the last decade, could explain the clinical characteristics of our stroke population. 26,27 From this standpoint, the possible presence of a selection bias is less plausible. We have prospectively validated our findings in another sample of stroke patients to be confident that our findings could be generalized beyond the group that we studied.…”
Section: Discussionmentioning
confidence: 99%